(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2006)
This article explores the significance and impact of embodiment theories of metaphor on some traditional formulations of the relationship between science and religion. For this purpose a methodology of metaphorical hermeneutics is implemented which shows metaphor and its underlying analogical structure to be significant keys to the understanding of the “metaphorical” nature of reality and cognition. Metaphorical models based on analogies are crucial hermeneutical keys to the understanding of reality. It is argued that specific analogical elements in these models acquire a guiding and controlling function in the process of theoretical understanding of phenomena. The relationship between a “basic metaphor” which provides the categories in terms of which the “world” is seen and the specific type of metaphorical control beliefs that function in a “religious” fashion in concept formation and theorizing is of interest in this article. These control beliefs condition the metaphors and analogies regarded as acceptable for the articulation of the structure of the explanandum, provide a “way of speaking” about phenomena and structure the generation of hypotheses and formation of concepts in theorizing. Fiduciary beliefs penetrate theories via a set of such core beliefs and function in a “religious” fashion. This refers to the way these beliefs are held and not to their content. The perspective on any phenomenon changes when the set of guiding beliefs that acquire primacy and determine the focus of the metaphor, changes.